Influence of hydrated lime and bitumen on different lateritic soil samples: case study of Sheda-Abuja, Nigeria - Ehizemhen C, Igibah; Lucia O, Agashua; Abubakar A, Sadiq (International Journal of Engineering and Technology, 2020)
This research was performed so as to appraise strength and properties of lateritic soils enriched with hydrated lime and bitumen as construction materials. Soil samplings S1, S2, S3, S4, and S5 was collected from Dualization of Sheda - Abaji, Abuja, F.C.T, Ni-geria and augment with 0, 3, 6, 9, and 12% of hydrated lime and bitumen. Laboratory tests like Consistency (Atterberg limit), California Bearing Ratio (C.B.R), compaction and sieve scrutiny were done on the soil sampling. The study exposed that construc-tive effects were gotten via the addition of hydrated lime and bitumen in order to augment the strength of weak soils. All the 5 samplings have C.B.R values of 48.0% with hydrated lime as additives, whereas bitumen additive is 40.60%. Introduction of addi-tives enriched the soil samplings from weak materials to an excellent base material with C.B.R values above 40%. Hence, aug-mentation of lateritic soil samplings from the studied locality could be perform efficiently by using lime.Â Â
Keywords: Hydrated Lime; Bitumen; Strength; Lateritic Soils; Atterberg Limit.